Studies on bacterial association with Amblyomma variegatum (Fabricius, 1974) (Acarina: Ixodidae) (1990)
Amblyomma variegatum, a haematophagus estoparasitic arthropod, is a known vector of several protozoan, bacterial, rickettsial and viral parasites of livestock. Being a 3-host tick , the larvae, nymphs and adults are active in transmitting these microorganisms. In this study, four bacteria Staphylococcus pyogenes, Enterobacter alvei, Escherichia coli and Klesbsiella rhinoscleromatis were isolated from the haemolymph of A variegatum detached from trade cattle. Staphylococcus pyogenes and Klebsiella rhinoscleromatis were found in the egg and larval extracts. It was observed that these two bacteria are transmitted transovarially by A. variegatum.